حساسية فطر التعفن الاخضر المعزول من الحمضيات تجاه بعض املاح البيكاربونات - محمد, صبرية عبد علي (University of Thi-Qar Journal of Science, 2013)
This study have been done to know the sensivity of the fungus Penicillium digitatum (Pers.:Fr)Sacc.toward some bicarbonat salts ( NaHCO3 , KHCO3 and NH4HCO3 ) at various concentration rangedbetween( 0.0 – 100.0)mM . The result indicates that the three salts give clear effect to inhibit fungalcolonies growth. There were a reversiabl relationship between the salts (bicarbonate) concentration and themeans of redial growth of colony. 10.0mM was gave the minimum growth inhibition while 50.0mM gavethe maximum growth inhibition. There were a reversiabl relationship between pH and the mean of redialgrowth.The minimum growth inhibition was at pH = 7.0 while maximum growth inhibition was at pH = 10.0.There were a clear effect on colony diameter when there were an interaction occure between pH andsalts concentration , at 0.0mM concentration ,the minimum growth inhibition was at pH = 6.0 whilemaximum growth inhibition was at pH = 8.5 . , at 5.0mM concentration ,the minimum growth inhibitionwas at pH = 4.5 while maximum growth inhibition was at pH = 8.5 , at 25.0mM concentration ,theminimum growth inhibition was at pH = 4.5 while maximum growth inhibition was at pH = 8.5 , and at50.0mM concentration ,the minimum growth inhibition was at pH = 4.5 while maximum growthinhibition was at pH = 8.5 .